2016
DOI: 10.1007/s00261-016-0730-y
|View full text |Cite
|
Sign up to set email alerts
|

Can diffusion-weighted magnetic resonance imaging predict tumor recurrence of uterine cervical cancer after concurrent chemoradiotherapy?

Abstract: Tumor ADC changes between preTx and midTx might be a useful biomarker for the prediction of cervical cancer recurrence after CCRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
0
15
2
Order By: Relevance
“…However, Heo et al [ 4 ] reported just the opposed results. Somoye et al [ 8 ] and Bae et al [ 9 ] also reported that pre-treatment ADC mean did not show any differences between good and poor long-term prognoses in cervical cancers. This discrepancy may be due to the following explanations: (1) the ROI placement with or without necrotic area in the tumors, while our study drew VOIs of the whole tumor (including cystic and necrotic areas) instead of traditional ROI (only one slice); (2) tumor heterogeneity, while our study contains various ADC histogram and texture parameters which can reflect the tumor heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Heo et al [ 4 ] reported just the opposed results. Somoye et al [ 8 ] and Bae et al [ 9 ] also reported that pre-treatment ADC mean did not show any differences between good and poor long-term prognoses in cervical cancers. This discrepancy may be due to the following explanations: (1) the ROI placement with or without necrotic area in the tumors, while our study drew VOIs of the whole tumor (including cystic and necrotic areas) instead of traditional ROI (only one slice); (2) tumor heterogeneity, while our study contains various ADC histogram and texture parameters which can reflect the tumor heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, we found that mid-CCRT ADC mean had a good prognostic value for patients with cervical cancers. Bae et al [ 9 ] also reported that mid-treatment ADC mean was significantly lower in tumor recurrence group and could serve as a useful prognostic biomarker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have compared pre-treatment ADC values in patients with versus without later tumour recurrence, finding that low pre-treatment ADC values seem to be a strong predictor of later tumour recurrence [ 22 , 101 – 107 ]. Furthermore, changes in ADC values during chemotherapy, radiotherapy or chemoradiation may help evaluate the treatment response [ 42 , 43 , 108 123 ]. For example, Kuang et al [ 42 ] examined 75 patients prior to, during and after therapy completion and found significantly higher ADCs in patients with complete response compared to those with partial response or stable disease after therapy completion.…”
Section: Tumour Recurrence and Therapeutic Responsementioning
confidence: 99%
“…Moreover, it may be possible to predict a possi-ble early recurrence based on DWI: A study from the year 2016 showed significant differences in ADC values between patients with tumor recurrence and patients without recurrence during radiochemotherapy treatment. A lower increase in ADC values during treatment was seen in patients with recurrence compared to patients without recurrence [37].…”
Section: Diagnosing Recurrencementioning
confidence: 77%